NILAI-NILAI PEDULI SOSIAL DALAM KURIKULUM AL ISLAM KEMUHAMMADIYAH DAN BAHASA ARAB STUDI MATA PELAJARAN AKIDAH AKHLAK SMA/SMK - Himatul Awwaliyah; Sutarman (LP2M Universitas Adzkia, 2022)
Abstract That the development of the era of young people now completely ignores the value of social care in this era of the covid-19 pandemic. Therefore, as teachers and parents should advise and educate to care for each other and change their morals for the better. This study uses a type of qualitative research research with a library research approach using data collection techniques or documents that researchers do on books, journals, articles, theses, and so on that are relevant to this research. These data are then analyzed in order to answer the problems in this study. The results of this study indicate that: (1) In providing education, students must have guidelines that should be followed by students: (2) it is necessary to have an understanding of the inculcation of the value of social care in the Al-Islam Kemuhamdiyahan curriculum and Arabic language and students' morals: (3) How to benefit and apply social care values ​​to character values ​​education in the era of the covid 19 pandemic. which is applied in everyday life.